Changes in placing organic functions in structure of German concern subsidiary = Zmiany w rozmieszczeniu funkcji organicznych w strukturze spółki zależnej niemieckiego koncernu - Sobotkiewicz, Dariusz (Zielona Góra: Faculty of Economics and Management Press)
This work focuses on changes in placing organic functions in organizational structure multi-entity enterprise. This problem is important, still up-to-date, especially in face of quick changes taking place in modern organizations? surroundings. This work aims at recognition of directions of changes in placing organic functions and identification of factors causing those changes taking as an example a German concern subsidiary. The theoretical part focuses on defining main change directions in placing functions. Great attention is paid to presenting different varieties of function shifts in economic organism. The empirical part deals with identification of changes that took place in placing functions and identifying the factors causing those changes.
Keywords: parent unit; subsidiary; organic functions; subfunctions; functionlocalisation/placement; jednostka nadrzędna; jednostka zależna; funkcje organiczne; subfunkcje; lokalizacja funkcji